Spirit Kerja Karyawan Masa Pandemi Covid 19 - Onsardi Onsardi; Lia Putri Elyanti Putri Elyanti; Ratnawili Ratnawili; Silvi Juwita (Journal of Management and Bussines (JOMB), 2022)
This study aims to analyze workload, work discipline and work motivation on the work spirit of Curup Prison, Bengkulu Province. This research method is quantitative. The objects in this study were Curup Prison employees, totaling 93 people. The sampling technique in this study is the saturated sampling technique. Data collection techniques using observation by distributing questionnaires. There are several data analysis techniques used in this study, including using instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that the workload pvalue was 0.043 < alpha was 0.05; b) work discipline has a pvalue of 0.001 < alpha 0.05; c) work motivation from the results of the analysis has a pvalue of 0.000 <alpha 0.050. In conclusion, the workload variable has a negative and significant effect on morale. Work discipline and work motivation have a positive and significant impact on morale. Simultaneously workload, work discipline, and work motivation have a significant effect on the morale of Curup Lapas employees. Keywords: Workload, Discipline, Motivation, Morale